Što je to vrijeme? Promišljanja o definiranju, značenju, kategorijama i mjerilima vremena (Filološke pripombe, 2019)
The essay entitled What is Time? Some Thoughts about the Definitions, Meaning, Categories, and Measurments of Time displays temporality at the forefront of contemporaty scolarly inquiry across the natural sciences and the humanities, for the study of time has fuelled a rapidly growing exchange of ideas between different disciplines. The author argues that various aspects of time form an integral part of our lives. Some have to do with control and measurement, others with ordering, synchronisation, sequencing, or timing, and still others with the time aspects of machines and artefacts. Thus, this essay approaches the whole spectrum of times as perceived in various interrelated disciplines like history, philosophy, language, myth, physics, and narratology; because time is constituted at every level of existence. It also demonstrates how to grasp the multiplicity of temporality is to come to terms with the complexity of our time